Roots are key to increasing the mean residence time of organic carbon entering temperate agricultural soils. (18th July 2021) - Poeplau, Christopher; Don, Axel; Schneider, Florian
Abstract: The ratio of soil organic carbon stock (SOC) to annual carbon input gives an estimate of the mean residence time of organic carbon that enters the soil (MRTOC ). It indicates how efficiently biomass can be transformed into SOC, which is of particular relevance for mitigating climate change by means of SOC storage. There have been few comprehensive studies of MRTOC and their drivers, and these have mainly been restricted to the global scale, on which climatic drivers dominate. This study used the unique combination of regional‐scale cropland and grassland topsoil (0–30 cm) SOC stock data and average site‐specific OC input data derived from the German Agricultural Soil Inventory to elucidate the main drivers of MRTOC . Explanatory variables related to OC input composition and other soil‐forming factors were used to explain the variability in MRTOC by means of a machine‐learning approach. On average, OC entering German agricultural topsoils had an MRT of 21.5 ± 11.6 years, with grasslands (29.0 ± 11.2 years, n = 465) having significantly higher MRTOC than croplands (19.4 ± 10.7, n = 1635). This was explained by the higher proportion of root‐derived OC inputs in grassland soils, which was the most important variable for explaining MRTOC variability at a regional scale. Soil properties such as clay content, soil group, C:N ratio and groundwater level were also important, indicating that MRTOC is driven by a combination of site properties and OC input composition. However, the great importance of root‐derived OC inputs indicated that MRTOC can be actively managed, with maximization of root biomass input to the soil being a straightforward means to extend the time that assimilated C remains in the soil and consequently also increase SOC stocks. Abstract : The ratio of soil organic carbon (SOC) stocks and annual OC inputs provides an estimate of how efficiently OC is stabilised in the soil. We applied this ratio, named the 'mean residence time of OC entering the soil' (MRTOC ) to a total of 2100 German agricultural topsoils and explained its variability by OC input characteristics and other soil forming factors using machine learning. The proportion of root‐derived OC input was most important, which also drove the higher MRTOC of grasslands (29.0 ± 11.2) as compared to croplands (19.4 ± 10.7). Maximising root input is an efficient measure to increase SOC and MRTOC.